2006
DOI: 10.1021/la061984u
|View full text |Cite
|
Sign up to set email alerts
|

Microscale Correlation between Surface Chemistry, Texture, and the Adhesive Strength ofStaphylococcusepidermidis

Abstract: Staphylococcus epidermidis is among the most commonly isolated microbes from medical implant infections, particularly in the colonization of blood-contacting devices. We explored the relationships between surface wettability and root-mean-square roughness (Rq) on microbial adhesive strength to a substrate. Molecular-level interactions between S. epidermidis and a variety of chemically and texturally distinct model substrata were characterized using a cellular probe and atomic force microscopy (AFM). Substrata … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 47 publications
2
75
0
Order By: Relevance
“…Conversely, other authors have reported that that an increase in the nanoscale roughness of the substrate surface leads to a decrease in the extent of bacterial attachment, 12,[17][18][19] and even a decrease in bacterial adhesion when nano-to micrometer scales are considered. 20 These apparently conflicting and contradicting studies highlight the need for the development of a platform that can produce homogeneous nanotopography that does not alter the chemistry of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, other authors have reported that that an increase in the nanoscale roughness of the substrate surface leads to a decrease in the extent of bacterial attachment, 12,[17][18][19] and even a decrease in bacterial adhesion when nano-to micrometer scales are considered. 20 These apparently conflicting and contradicting studies highlight the need for the development of a platform that can produce homogeneous nanotopography that does not alter the chemistry of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Force spectroscopy approaches using atomic force microscopy (AFM) [9] have provided novel information on cell adhesion, particularly at the single-molecular level, and on the nanomechanical properties of cells [10]. Single-cell force spectroscopy (SCFS) of eukaryotic [11][13] and prokaryotic [14], [15] cells, which are attached to the end of a tipless AFM cantilever, allows the quantification of the adhesion force of the entire cell to a given substrate and makes possible the study of the contribution of distinct molecular classes to the overall adhesion event [10]. This force quantification helps unravel the adhesion-related gene products, mechanisms and regulatory signals [16].…”
Section: Introductionmentioning
confidence: 99%
“…The author then moved this on to look at the adhesion of fungal and bacterial spores [77,78]. Protocols for the construction of cell probes have varied in the method of cantilevers functionalization: electrostatic compounds; poly(ethyleneimine) (PEI), poly-L-lysine, or hydrophobic substances, and the use of glue, chemical fixation, and bio-inspired wet adhesives have all been used, and in the type of probe that was created: single versus multicellular [3,[79][80][81][82][83][84][85]. While all methods succeeded in the creation of a cellular functionalized tip and the acquisition of adhesive force-curve data, the results and validity of the techniques varied.…”
Section: Single-cell Force Spectroscopymentioning
confidence: 99%